Development, validation and evaluation of guided-imagery and relaxation audio for children - Othman, Azizah; Buang, Muhammad Junaidi; Taib, Mai Nurul Ashikin; Mohamad, Norsarwany; Nasir, Ariffin (2012)
Guided imagery and relaxation (GIR) involves generation of positive sensation and emotion through mental imagination to induce a state of psychological and physiological relaxation. Objective: To develop, validate and evaluate a GIR audio for children in Bahasa Malaysia. Methods: Based on extensive review, GIR script was developed by a clinical psychologist. Panels of experts including pediatric oncologists and psychiatrist conducted initial assessment at multiple stages of hearing sessions. The final version of the audio was pre-recorded in MP3 player for evaluation. Results: Face and content validation of 3 x 5 minutes duration of GIR audio were obtained via experts’ reports. Twenty-three participants (5 adults, 18 children) listened to the audio and completed evaluation form. All adult evaluators gave positive remarks on the script, narration and recording quality. As for the children, 100% completed audio-hearing and majority (66.7% – 88.9%) was able to imagine well without falling asleep and in some way affected by the imagery-induced relaxation audio. Majority was not disturbed during the hearing sessions (66.7%), will hear it again (83.3%) and found it enjoyable (88.8%). Conclusion: This is the first known study developing GIR audio in Bahasa Malaysia which is feasible, enjoyable and beneficial for children that warrants efficacy study.